QIRĀ`AT SHĀDHAH DALAM TAFSIR SYIAH: Studi Term Nikah Mutâ€™ah dan Imam - Ahmad Musonnif Alfi (STAI AL-ANWAR SARANG, 2018)
This study tries to investigate the use of qirā`at shādhah in Shia interpretation. The discussion about qirā`at shādhah in the study of al-Qur`an exegesis is still interesting to examine. It is indicated that different perspectives can affect the realization of understanding the Qur'an. This can be seen, for example, in the debates of al-Shāfi'i and Mālik with Abū Ḥanīfah and Aḥmad in understanding surah al-Māidah verse 89 which explains about the fine for violation of oaths which results different legal products. The use of qirā`at shādhah seems to have also been of concern to the Shi'ah interpreters. Al-Ṭabāṭabā'ī for example in al-Mīzan fi Tafsīr al-Qur'ān stated that permissiveness of mut'ah marriage was mentioned in the QS. al-Nisā 'verse 24 which was corroborated by qirā`at shādhah Ubay bin Ka'ab, Ibn Mas'ūd, and Ibn Abbās. Meanwhile, al-Shawkānī Shi'a scholar taking the Zaidiyyah thought, argued otherwise. Nikah mut'ah is not allowed because the argument is interrogated (mansūkh). This means that qirā`at shādhah is also an important term for the Shi'ah group to be used as a tool for analysis in producing new laws in the products of their interpretation. Therefore, this paper will look at how the existence of qirā`at shādhah in Shia Interpretation work, especially the differences between their scholars regarding it. In addition, the discussion of qirā`at in Shi'ah is still rarely found. As a comparison, this paper will describe the terms nikah mut'ah and imāmah.